Indigenous Uses of Plants among Forest-dependent Communities of Seijosa, Arunachal Pradesh - Balkrishna, Acharya; Joshi, Bhasker; Srivastava, Anupam; Shukla, B. K.; Shankar, Rama; Kumar, Amit; Aqib; Kumar, Aashish; Prajapati, Uday Bhan; Mishra, Rajesh Kumar (International Journal of Economic Plants, 2022)
The present paper explores the dependence of local population of Seijosa circle of Pakke-Kessang district, Arunachal Pradesh on the phytoresources available here. Local population of Sejiosa circle has their unique system of resource management. They are directly dependent on their surroundings for timber forest products (TFPs) and non timber forest products (NTFPs). This area is rich in vascular plant diversity which direcly or indirectly supports wild life also. In present study total 365 plant species belonging to 272 genera and 95 families have been recorded, which are utilized by natives of this area in the form of beverage, broom making, canes, condiment / spices, craft, dye, edible (fruit), fiber, fodder, fuel, medicinal, oil, ornamental, paper pulp, resin, tannin, timber, vegetable, etc.